The Identity of Islamic Women in Online Media: A Study Confirming The Message of The Digital Identity of Progressive Women in Suara ’Aisyiyah - Destita Mutiara (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2023)
Suara 'Aisyiyah is a magazine that has been published and managed by the central board of 'Aisyiyah for 96 years with the tagline “The Inspiration of Progressive Women”. This magazine has been an outlet of the ‘Aisyiyah members to express their ideas and to promote their movements, which they consider progressive. The purpose of this study is to investigate the progressive messages of ‘Aisyiyah members through the messages that have been published in Suara 'Aisyiyah's online media, especially its website and Instagram. By using a narrative content analysis, this study shows that the digital identity of Suara 'Aisyiyah refers to the 'Aisyiyah organizational view. The identity of the progressive women is confirmed through the display of writing rubrics in the website including News Rubric, Opinion, Sakinah Family, Insights, Lifestyle, and Youth Inspiration. This progressive identity is also found in the Infographics Display on Instagram with an emphasis on the message of equal rights of men and women and the freedom of humans from gender discrimination.